The Role of Restorative Justice in Juvenile Criminal Law Islamic Law Analysis - Permana, Yudhi; Marpaung, Watni; Harahap, Arifuddin Muda (JURNAL AKTA, 2025)
The Restorative Justice (RJ) approach in juvenile criminal law is a paradigm that is oriented towards the restoration, reconciliation, and rehabilitation of children in conflict with the law. Unlike the retributive justice system which emphasizes punishment, RJ aims to restore social balance through deliberation between the perpetrator, victim, and community. In Indonesia, the RJ principle has been accommodated in Law No. 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA) which prioritizes diversion as a mechanism for resolving juvenile cases outside the courts. In addition, the Indonesian Attorney General's Regulation Number 15 of 2020 also regulates the termination of prosecution based on restorative justice. From an Islamic legal perspective, the RJ approach is in line with the principle of Maqashid Syari’ah, which aims to protect the soul (hifz al-nafs) and maintain social harmony. The concepts of qisas, diyat, sulh, and afw in Islam provide space for a more just conflict resolution, emphasizing forgiveness and peace as the main solutions in resolving criminal cases, including for children. The implementation of RJ in the Indonesian legal system faces several challenges, such as the lack of understanding of law enforcement officers, the limitations of more comprehensive regulations, and the minimal involvement of the community in the reconciliation process. Therefore, this study recommends strengthening regulations by enacting a special law on RJ, increasing training for law enforcement officers, and public education so that the community's understanding of restorative justice increases. With these steps, RJ can be an effective solution in a more just juvenile criminal law system, in accordance with Islamic legal values.